External auditory canal osteoma: a case report (Journal of Health Sciences, 2017)
Osteoma is benign tumor composed of well- differentiated matured osseous tissue. Its presence in mandible and paranasal sinuses is common, yet appearance in external auditory canal is rare. We present a case of a 26- year- old male complaining of hearing loss and pain in the affected ear. Pathohistological analysis of surgically removed tissue revealed tumor consisted of mature trabecular bone, which represents benign lesion without tendency of metastasis.